Immune surveillance for vaccine-preventable diseases. (2nd April 2020) - den Hartog, Gerco; van Binnendijk, Rob; Buisman, Anne-Marie; Berbers, Guy A. M.; van der Klis, Fiona R. M.
ABSTRACT: Introduction: Immunesurveillance is an important tool to monitor the protection of the population against vaccine-preventable diseases, which is currently mostly based on the detection of specific serum antibodies. However, the landscape of immune surveillance is changing, driven by emerging and evolving pathogens, changes in the age distribution of the population and scientific understanding of protective immunity, necessitating a comprehensive review. Areas covered: To anticipate these changes, reliable and high-throughput detection of antibody levels is desired to enable screening in larger population settings. Antibody levels alone do not always equate with protection and may require additional functional testing of the antibodies or immune cell-based assays. In addition, the location (systemic or locally mucosal) of the infection and whether the antibodies are induced through infection or vaccination have implications for both immune protection and assessing immune status. Expert commentary: In order to perform multicenter studies on many samples for multiple antigens, more validated reference materials and wider adoption of high-throughput techniques are needed. The field of serosurveillance will also benefit from better correlates of protection and understanding of (local) mechanisms of protection. Here we give an overview of the current state-of-the-art of serosurveillance and how the field could move forward.